Eficiência energética em rede de trocadores de calor: análise termodinâmica e elétrica do bombeamento de fluido de troca térmica - CARNEIRO, Manasses Guimarães (2016)
The cost of electricity in Brazil increased considerably during the 2015-2016 biennium, largely as a result of the water crisis that began in 2012. Associated with this, country economy is undergoing a severe recession and presented a 3.8% shrinkage in 2015 with a 3.3% outlook for 2016. This triggered a strong reduction of the country's industrial activity, unemployment increases and consumption reduce. As a result, efficiency processes are being sought with the aim of reducing fixed expenses and thus increasing net profits of the productive sectors. In industry, the electric motors energy consumption, corresponds to approximately 68% of total, this sector, in turn, consumes 32.5% of all country’s electric energy used; It is natural that electric motors are the priority in investments to energy consumption reducing. A great part of the energy spent by electric motors is due to operating inefficiencies and of the process in which they are inserted. Based on this, the present dissertation has the goal of demonstrating that savings in electric energy can be obtained when there is a variable flow demand for a given process, using the pumping water process to a network of heat exchangers as an example. The saltwater heat exchanger system of the Madre de Deus Terminal was used as a case study, where analyzes of the thermal exchange process and operational procedures were performed, as well as current energy expenditure measurements; finally, the efficiency perspective was obtained with the use of PWM frequency inverters associated to operational changes. From the results it was realized that, electric energy savings with the implementation of variable speed drives and change in operating procedures could be R $ 32,205.48 reais per month, which is considered relevant to current conditions in the industrial sector. Currently 78% of the energy spent is not needed, the investments time to return through net present values was 23 months, less than two years for the case study.